Study of some soils of the Himalayan piedmont plain of Bangladesh - Uddin, MJ; Hasan, MK; Mohiuddin, ASM; Ahmed, SU; Hassan, MM (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Results of four representative pedons of the Old Himalayan piedmont, collected horizonwise from Thakurgaon district, revealed that the color of the topsoil was dark grayish brown to dark yellowish brown and that of the subsoils was dark yellowish brown to light olive-brown and light brownish grey when moist. The soils have moderately well drained conditions except Baliadangi soils which are imperfectly drained. Prismatic to subangular blocky structure has been developed in subsurface horizons of all the profiles, whereas massive structure was found in the surface horizons. Sand was by far the dominant fraction in the soils. The texture of the soils varied from clay loam to sandy loam. The irregular vertical distribution patterns of sand/silt ratio in the profiles indicate the heterogeneous nature of the parent materials. The pH of the soils ranged from 5.4 to 6.26. The organic matter contents as well as total nitrogen of these soils were, in general, low. The C/N ratios of the soils varied from 4.3 to 10.3. The cation exchange capacity (CEC) in most of the studied soils were low. Calcium and magnesium were the dominant cations in all the soils. DOI: http://dx.doi.org/10.3329/jasbs.v38i2.15610 J. Asiat. Soc. Bangladesh, Sci. 38(2): 199-206, December 2012